18F-PBR06 Versus 11C-PBR28 PET for Assessing White Matter Translocator Protein Binding in Multiple Sclerosis. (September 2018) - Singhal, Tarun; O'Connor, Kelsey; Dubey, Shipra; Belanger, Anthony P.; Hurwitz, Shelley; Chu, Renxin; Tauhid, Shahamat; Kijewski, Marie F.; DiCarli, Marcelo F.; Weiner, Howard L.; Bakshi, Rohit
Abstract : Background and Purpose: 18 F-PBR06 and 11 C-PBR28 are second-generation PET radioligands targeting the 18-kd translocator protein to assess microglial activation. We directly compared 18 F-PBR06 and 11 C-PBR28 for detecting brain translocator protein binding in multiple sclerosis (MS). Methods: Six patients with MS (4 women; mean age ± SD, 32.1 ± 4.9 [range, 23.5–37.4 years]; Expanded Disability Status Scale score 2.3 ± 1.2 [range, 1.0–4.0]) underwent brain PET with both ligands, along with 3-T MRI. MRI was coregistered to the summed 60- to 90-minute PET images. SUV ratios (SUVRs), derived by normalization to global brain radioactivity, were obtained for whole-brain white matter (WM), supratentorial WM, normal-appearing WM (NAWM), and T2 (fluid-attenuated inversion recovery) hyperintense and T1 hypointense MS WM lesions. The highest mean SUVR for the fluid-attenuated inversion-recovery lesional slices was defined as SUVRmax. Results: 18 F-PBR06 and 11 C-PBR28 were moderately intercorrelated for whole-brain WM SUVR ( r = 0.83, P = 0.04) and supratentorial WM SUVR ( r = 0.81, P = 0.05) but not for SUVRs of NAWM, T1 lesions, T2 lesions, or SUVRmax. Both tracers demonstrated that SUVR was higher in NAWM than in T1 and T2 lesions (all P < 0.05). 18 F-PBR06 (but not 11 C-PBR28) demonstrated a higher SUVR in T1 versus T2 lesions (0.85 ± 0.07 vs 0.78 ± 0.03, P = 0.03). 18 F-PBR06-derived (but not 11 C-PBR28) SUVRmax correlated with both Expanded Disability Status Scale score ( r = 0.82, P = 0.04) and timed 25-ft walking speed ( r = 0.89, P = 0.01). Conclusions: Our preliminary results suggest an association between microglial activation and physical disability in MS. Microglial detection in lesions was not interchangeable between the tracers, with a higher clinical relevance suggested for 18 F-PBR06.